Study on Purchasing Behaviour of Customers for Essential Goods Through E-Commerce Amidst COVID-19 Pandemic - Sawarkar, Shruti Sadanand (Indian Journal of Computer Science, 2021)
COVID-19 pandemic has created an opportunity to study the buying behavior of online shoppers towards the purchase of essentials goods. They are willing to experience and try new technology. Given the growing importance of the online retail industry in India, it becomes imperative for web retailers and internet marketers to understand the determinants of purchase intention of online customers to decipher what is important for Indian online customers. This paper attempts to identify the determinants of online purchase intention among youth in the Indian context. Methodology : Primary data were collected through Google forms from 194 respondents. Findings : People from different tiers purchased essential goods online. 28% of respondents shifted towards online purchasing. There are no interesting offers provided online. There is a significant relationship between the satisfaction of customers and the frequency of purchase of essential goods. Research limitations/implications : A bigger and more representative sample that includes respondents from all walks of life would have been appropriate, though the internet savvy students contribute the major share of online buyers